2014
DOI: 10.1021/cs500733j
|View full text |Cite
|
Sign up to set email alerts
|

Pt/SBA-15 as a Highly Efficient Catalyst for Catalytic Toluene Oxidation

Abstract: The catalytic oxidation of toluene has been investigated using a series of Pt/SBA-15 and Pt/SiO 2 catalysts, and the Pt/SBA-15 catalyst exhibits significantly higher catalytic activity for the oxidation of toluene than the Pt/SiO 2 catalysts. The SBA-15-supported Pt nanoparticles possess the ability to strongly dissociate toluene to benzene, hydrocarbon fragments (CH x ), and H 2 at low temperatures, but the Pt/SiO 2 catalysts are nonreactive toward the decomposition of toluene. The products resulting from the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
75
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 153 publications
(80 citation statements)
references
References 55 publications
3
75
2
Order By: Relevance
“…Nevertheless, positive adsorption entropy (100 J mol −1 K −1 ) and enthalpy (8 kJ mol −1 ) values were obtained, thereby indicating the occurrence of endothermic adsorption, which is uncommon for catalytic reactions [24,25].…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, positive adsorption entropy (100 J mol −1 K −1 ) and enthalpy (8 kJ mol −1 ) values were obtained, thereby indicating the occurrence of endothermic adsorption, which is uncommon for catalytic reactions [24,25].…”
Section: Introductionmentioning
confidence: 99%
“…Generally, noble metals such as Pt and Pd have been found to show very high activity and selectivity towards catalytic total oxidation of VOCs [11][12][13][14][15]; however, these are known to be expensive and therefore, more economic alternatives have been searched for the last several decades [16][17][18][19][20]. It has been found that less expensive materials such as Mn-oxide, Cu-oxide and Ni-oxide can also show substantially high activity towards oxidation of VOCs [16,[20][21][22][23][24][25].…”
Section: Introductionmentioning
confidence: 99%
“…It can be attributed to the shrinkage of SBA-15 framework accompanied by a decrease in the cell parameter a 0 due to the formation of reduced Pd species. [42] Figure 4B shows the wide- 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 angle XRD patterns of samples. A broad diffraction peak at 2θ � 22°was observed in all samples, which was assigned to amorphous silica of SBA-15.…”
Section: Resultsmentioning
confidence: 99%